Impact performances and failure modes of glass fiber reinforced polymers in different curvatures and stacking sequences. (March 2022) - Kaboglu, Cihan; Eken, Taha Y; Yurekturk, Yakup
Recently, glass fiber reinforced polymer composites have been increasingly used in applications which are exposed to impact loads due to their high strength, low weight, and corrosion resistance properties. Therefore, the effect of curvature of composite laminate on their impact resistance is important. In this study, the mechanical properties of three curvature diameters and two stacking sequences, which have not been compared before, were examined and compared. The diameter of curved composites is 760 mm, 380 mm, and 304 mm and flat designated as A, B, C, and D, respectively. The fiber stacking orders are [0/0/-45/+45/90/90]S and [90/90/-45/+45/0/0]S designated as Type 1 and Type 2, respectively. The drop-weight impact tests were performed and failure modes of composites were examined. It was observed that the impact resistance decreases with the increase of curvature, where 760 mm diameter and Type 2 composites had the highest strength in all of the composites. In addition, delamination, fiber breakage, and matrix cracking failure modes were observed in the composites after impact. The reason why the strength decreases as the curvature of the composite increases is that the curved areas create an effect that increases the external force applied. The reason why Type 2 stacking order is more durable than Type 1 stacking order is that the 90° fiber direction in the bottom layer has a damping effect on the applied force. According to the results of this study, composite materials with larger diameter and stacking order starting with 0° provides more mechanical strength.